2020
DOI: 10.9734/acri/2020/v20i230172
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus in School Age Children Seen at the University of Port Harcourt Teaching Hospital: A Need for Booster Doses of Tetanus Vaccine

Abstract: Background: Tetanus still causes significant morbidity and mortality amongst children in Nigeria despite decades of immunisation with tetanus vaccine. Objectives: To determine the prevalence, case fatality rate and predictors of fatality amongst school age children treated for tetanus at the University of Port Harcourt Teaching Hospital. Materials and Methods:  This was a retrospective study of all children aged 4 to 17 years treated for tetanus at the University of Port Harcourt Teaching Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
(51 reference statements)
2
4
0
Order By: Relevance
“…The fact that the commonest portal of entry in this study was from traumatic injuries corroborates it. The higher prevalence of PNT among male children as observed in this study is well documented in other studies [26][27][28][29][30] and this has been alluded to males being more involved in outdoor activities and therefore more prone to injuries than their female counterparts.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The fact that the commonest portal of entry in this study was from traumatic injuries corroborates it. The higher prevalence of PNT among male children as observed in this study is well documented in other studies [26][27][28][29][30] and this has been alluded to males being more involved in outdoor activities and therefore more prone to injuries than their female counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…The same observation was also noted by earlier studies reported by Yaguo Ide et al [8] in Port Harcourt and in other studies carried out in Nigeria, [26,27,29,31] and Ethiopia. [33] It is quite interesting that the mean age of the study population of 10±2.68 years, similar to that reported in other studies in the country [28][29][30] may be contributory to the higher incidence of PNT among children in the older age groups. It is pertinent to note that the 3 doses of tetanus toxoid vaccine given to infants in the primary immunization series in Nigeria protects them from tetanus for about 3-4 years.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations